2020
DOI: 10.1038/s43016-020-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis engineered to increase rice yield

Abstract: An engineered increase in Rubisco production has increased photosynthetic capacity, rice yield and nitrogen use efficiency in an experimental paddy field. This demonstrates a key means to sustainably increasing yield and global food security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This parallels the previous findings for rice leaves in the vegetative growth stage ( Acevedo-Siaca et al , 2020 ) and suggests that the predominant limitation to photosynthetic CO 2 assimilation at steady state and non-steady state throughout the life cycle of rice is consistently due to the in vivo capacity and, presumably, amount of Rubisco. This is also consistent with the recent observation that transgenic up-regulation of Rubisco in rice significantly increases paddy yield ( Long, 2020 ; Yoon et al , 2020 ). One caveat is that this analysis is based on C i and not the CO 2 concentration at Rubisco ( C c ).…”
Section: Discussionsupporting
confidence: 93%
“…This parallels the previous findings for rice leaves in the vegetative growth stage ( Acevedo-Siaca et al , 2020 ) and suggests that the predominant limitation to photosynthetic CO 2 assimilation at steady state and non-steady state throughout the life cycle of rice is consistently due to the in vivo capacity and, presumably, amount of Rubisco. This is also consistent with the recent observation that transgenic up-regulation of Rubisco in rice significantly increases paddy yield ( Long, 2020 ; Yoon et al , 2020 ). One caveat is that this analysis is based on C i and not the CO 2 concentration at Rubisco ( C c ).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that enhancement of photosynthesis is of the greatest importance for a further increase in the yield of high-yielding cultivars with a large sink size. While there has been a dispute as to whether photosynthesis improvement leads to an increase in cereal crop yields 35 , we have actually shown that an increase in photosynthesis by overproducing Rubisco results in increased rice yields under field conditions 36,37 Thus, improving photosynthesis is a possible target for realizing a further increase in yield of today's high-yielding cultivars. www.nature.com/scientificreports/ conclusions The world's population is now exponentially increasing and is predicted to reach 10 billion by the middle of this century.…”
Section: Discussionmentioning
confidence: 84%
“…Photosynthesis is considered to be a key process that determines N response and NUE in crops ( Long, 2020 ), through the regulation of associated genes in rice ( Kumari et al, 2021 ; Sharma et al, 2021 ; Mandal et al, 2022 ). We sought to further validate these findings using contrasting genotypes in this study.…”
Section: Discussionmentioning
confidence: 99%